O mito e o trágico em Jim Morrison: a poesia como choque e redenção da história - Assis, Dráulio Carvalho (2015)
This dissertation seeks to reveal through the poetry of James Douglas Morrison, best known for becoming a myth as lead singer of the American band The Doors in the sixties, the dilemma of its historic man of conflicts and man mythological in his tragic search cross to the other side, so, a different view of the hegemonic vision of society, a reconciliation as historical subject. Bring to light some thinkers who reflect on time, memory, myth, tragic and poetry that we have to tell us to outline as man sees the flow or interiority that time in your consciousness. Jim Morrison's poetry becomes a revelation that moment in which consciousness sees the flow of time in its interiority and shows continuity in anguish and identities. The revelation of a transcendent term becomes an illumination which aims to immanence, that is, the eternal now and what it can reveal itself in its duration. The historical reality is loaded and then builds images with mythological content profiling dreamily walking and the progress of actions, therefore, poetry imbued with allegorical images the capture and visualize, breaking standards and implementing utopian conceptions, opening doors and can outline a new ethos. Within this allegorical conception to Walter Benjamin, the historian has hidden the awakening of gift of the past with the now knowledgeability in an immediate correspondence with the redemption of history. According to Marcelo Marques myth acts ethically in human existence by its poetic force, the human making it possible thus demystify Jim Morrison in his poetry that reveals his anguish, show a more human face who sought redemption through poetry. Understanding this search on your "moment of now" at this intersection and past his poetic recall the world is opening doors to redemption of history, as glimpsed like lightning in the dark night the connection of past and present experiences in the eternal now. In his tragic poetry Jim Morrison reveals their looks, conflicts, unreasonable and his misfortune that are contemporary, as in Baudelaire, Rimbaud and other artists, with the gift of modern society. Poetry as crossing times becomes the wild eye and the tragic awareness that awakens the instant of now, allowing the redemption of continuity identities and anguish in the heart of the story.